Business guide to trade remedies in the European Community : anti-dumping, anti-subsidy and safeguards legislation, practices and procedures (ITC GenevaCH, 2004)
Highlights those aspects of the law and practice of the European Community and the appropriate provisions of the relevant WTO Agreements, which may be of practical interest to business managers, exporters and importers of developing countries and transition economies.
Bibliography: p. 207-209